Point-of-Care Thoracic Ultrasound in Trauma - O. Cook, Justin (Current Respiratory Medicine Reviews, 2015)
Point-of-care ultrasound is an increasingly utilized technology in the management of the acutely injured patient. Ultrasonography has demonstrated utility and improved outcomes in rapidly detecting pnemothorax, intrapericardial blood and assessing cardiac function in the hemodynamically unstable patient. Examination of the thorax incorporated into the FAST exam (termed E-FAST, or extended FAST exam) enables rapid recognition of pathology within the trauma bay, permitting earlier intervention.
Keywords: tamponade